Hepatitis C Virus Antibody Screening in a Cohort of Pregnant Women: Identifying Seroprevalence and Risk Factors. Issue 4 (April 2020) - Prasad, Mona; Saade, George R.; Sandoval, Grecio; Hughes, Brenna L.; Reddy, Uma M.; Mele, Lisa; Salazar, Ashley; Varner, Michael W.; Gyamfi-Bannerman, Cynthia; Thorp, John M.; Tita, Alan T. N.; Swamy, Geeta K.; et al.
Abstract : OBJECTIVE: To describe the prevalence of hepatitis C virus (HCV) antibody, evaluate current risk factors associated with HCV antibody positivity, and identify novel composite risk factors for identification of groups most likely to demonstrate HCV antibody seropositivity in an obstetric population from 2012 to 2015. METHODS: The Eunice Kennedy Shriver National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network initiated an observational study of mother-to-child transmission of HCV in 2012 that included offering HCV antibody screening to their entire obstetric population. Women presenting for prenatal care before 23 weeks of gestation without a known multifetal gestation were eligible. For each woman who was HCV antibody–positive, two women at similar gestational age who were HCV antibody–negative were identified and included for comparison. Risk factors were evaluated by patient interview and chart review. Women in the case group were identified to have a signal-to-cutoff value of at least 5 on the Abbott ARCHITECT platform. RNA status was evaluated for women in the case group. RESULTS: Of 106, 842 women screened for the HCV antibody, 254 had positive results. The HCV antibody seroprevalence rate was 2.4 cases per 1, 000 women (95% CI 2.1–2.7). One hundred thirty-one women in the case group and 251 women in the control group were included in the case–control analysis. Factors associated with HCV antibody positivity included injection drug use (adjusted odds ratio [aOR] 22.9, 95% CI 8.2–64.0), blood transfusion (aOR 3.7, 95% CI 1.3–10.4), having a partner with HCV (aOR 6.3, 95% CI 1.8–22.6), more than three lifetime sexual partners (aOR 5.3, 95% CI 1.4–19.8), and smoking (aOR 2.4, 95% CI 1.2–4.6). A composite of any of these potential risk factors provided the highest sensitivity for detecting HCV antibody (75/82 cases, 91%). CONCLUSION: In this cohort, the seroprevalence of HCV antibody was low, and the current risk factors for HCV screening were not identified. These findings may be useful in defining new strategies for identifying mothers with the HCV antibody and the neonates susceptible to maternal transmission of HCV. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01959321. Abstract : Screening an unselected obstetric population for hepatitis C virus did not identify a significant population on which to target intervention.